2019
DOI: 10.3390/healthcare7040160
|View full text |Cite
|
Sign up to set email alerts
|

Rural Resident Experience on National Basic Public Health Services: A Cross-Sectional Survey in 10 Western Provinces of China

Abstract: National basic public health services (BPHSs) are important for promoting the health of rural populations. A better understanding of rural BPHSs from the viewpoint of residents utilizing the services can help health-related departments and primary health care (PHC) centers further improve rural BPHSs. By conducting a large-scale cross-sectional survey in 10 western provinces of China, the study depicts rural resident experiences with rural BPHSs. Of the 9019 participants, 59.33% and 66.48% did not receive serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…These results suggested that providing health education or providing information on national BPHSs was not enough to establish health record in young Chinese migrants. Therefore, it is essential to adopt effective methods to implement health education and promotion in the community [ 18 , 31 ]. Specifically, materials about BPHSs should be posted in the publicity column of the community, to popularize the ways and functions of establishing health records, meanwhile, electronic information-based health education channels including the Internet and new media should be developed to improve the quality of health education.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that providing health education or providing information on national BPHSs was not enough to establish health record in young Chinese migrants. Therefore, it is essential to adopt effective methods to implement health education and promotion in the community [ 18 , 31 ]. Specifically, materials about BPHSs should be posted in the publicity column of the community, to popularize the ways and functions of establishing health records, meanwhile, electronic information-based health education channels including the Internet and new media should be developed to improve the quality of health education.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with migrants with rural household registration, migrants with urban household registration had a higher likelihood to utilize BPHS [5,7,16,17]. Other factors were also explored in the studies of this research domain, such as social integration, age, ethnicity, employment status, current health situation, medical insurance coverage, rage of migrating, family income were also associated with the utilization of BPHS [7,13,16,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focus on the fact that many residents migrated from rural areas to urban areas, which may have an impact on their utilization of health services, as there are more adequate health resources in urban areas [11,12]. The utilization of BPHS in rural areas are relatively low [13]. After moving to urban areas, the health literacy of migrants from rural areas has been improved and this promoted their participation in health education activities [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The professional staff of primary healthcare centers did not have enough time and energy to provide high-quality and enough health services. At the same time, during interviews with the staff of primary healthcare centers, we found that although the remuneration for providing services to each resident was increasing year by year, for some areas with inconvenient transportation, these remunerations may be less than the cost of providing services, which reduced their enthusiasm of providing services [9]. Compared with the migrants with rural household registration, the possibility of establishing health records was higher for migrants with urban household registration.…”
Section: Discussionmentioning
confidence: 90%